Study of Heat Transfer in Magnesium Zinc Zirconium MgZn6Zr Alloy Suspended in Engine Oil - Saima Noor; Safyan Mukhtar (Journal of Mathematics)
In this paper, alloy nanoparticle MgZn6Zr will be analyzed for the first time in the flow of ferromagnetic nanofluid. The combination of two or more metallic substances is termed as alloy. In other words, alloys are a solid solution or mixture of more than one metallic substance. Thus, alloys have always distinct melting points. This means that alloys have melting ranges instead of melting points. Due to these characteristics, alloy nanoparticles are efficient for heat transfer in liquid flows. Thus, we will consider magnesium alloy MgZn6Zr which is suspended in the base fluid engine oil C8H18. The suspension will be analyzed along a dipole; thus, the fluid is known as ferromagnetic MgZn6Zr−C8H18 nanofluid. Solutions will be obtained numerically through the RK-method (shooting method). Our motivation is to optimize the heat transfer through the parametric study. Further, velocity of the fluid is observed to be decreasing with increasing the volume fraction of nanoparticles while temperature profile gets a rise with increase in volume fraction. Moreover, the presence of alloys in any viscous base fluid can decline the fraction between certain fluid layers which results in fast velocity field for the proposed fluid.